2021
DOI: 10.1002/adma.202106633
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Resolution Imaging of Highly Curved Membrane Structures in Giant Vesicles Encapsulating Molecular Condensates

Abstract: Molecular crowding is an inherent feature of cell interiors. Synthetic cells as provided by giant unilamellar vesicles (GUVs) encapsulating macromolecules (poly(ethylene glycol) and dextran) represent an excellent mimetic system to study membrane transformations associated with molecular crowding and protein condensation. Similarly to cells, such GUVs exhibit highly curved structures like nanotubes. Upon liquid–liquid phase separation their membrane deforms into apparent kinks at the contact line of the interf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…It is thus plausible to assume that the kinks in Figure 3 will be replaced by a smoothly curved membrane segment on sufficient small length scales [ 5 ]. This assumption has been recently confirmed by super-resolution STED microscopy [ 52 ], see Figure 14 . In what follows, we will assume that all kinks in Figure 3 will be smoothened out when observed with sufficiently high resolution.…”
Section: Theory Of Curvature Elasticity and Vesicle-droplet Adhesionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is thus plausible to assume that the kinks in Figure 3 will be replaced by a smoothly curved membrane segment on sufficient small length scales [ 5 ]. This assumption has been recently confirmed by super-resolution STED microscopy [ 52 ], see Figure 14 . In what follows, we will assume that all kinks in Figure 3 will be smoothened out when observed with sufficiently high resolution.…”
Section: Theory Of Curvature Elasticity and Vesicle-droplet Adhesionsupporting
confidence: 61%
“…Therefore, each kink in Figure 3 should be replaced by a smoothly curved membrane segment on sufficiently small length scales [ 5 ]. Such smoothly curved segments have indeed been observed by super-resolution STED microscopy [ 52 ] as described further below.…”
Section: Contact Angles Of Adhesion Morphologiesmentioning
confidence: 76%
“…11 A ). To this end, we employed rectangular microfluidic traps ( 59 ) with a gap size of approximately 5 μm between the posts. This setup enabled hydrodynamic control over the LUV delivery, fast exchange of the outer solution, and immobilization of the GUVs.…”
Section: Resultsmentioning
confidence: 99%
“…An automated algorithm for GV structural assessment using confocal laser scanning fluorescence microscopy images was developed by García-Sáez’s group [ 19 ]. More recently, Dimova’s group developed observation techniques for GUVs based on stimulated emission depletion (STED) microscopy, which can provide a high spatial resolution beyond the diffraction limit of light [ 20 , 21 ]. They found that the deduced membrane spontaneous curvature of nanometer-sized vesicular tubes produced from GVs, was in excellent agreement with theoretical predictions.…”
Section: Identification Methods Of Gvsmentioning
confidence: 99%